Combined RASSF1A and RASSF2A Promoter Methylation Analysis as Diagnostic Biomarker for Bladder Cancer. (11th March 2012) - Meng, Wei; Huebner, Alexander; Shabsigh, Ahmad; Chakravarti, Arnab; Lautenschlaeger, Tim
Abstract : Promoter hypermethylation, a widely studied epigenetic event known to influence gene expression levels, has been proposed as a potential biomarker in multiple types of cancer. Clinical diagnostic biomarkers are needed for reliable prediction of bladder cancer recurrence. In this paper, DNA promoter methylation of five C-terminal Ras-association family members ( RASSF1A, RASSF2A, RASSF4, RASSF5, and RASSF6 ) was studied in 64 formalin-fixed paraffin-embedded (FFPE) bladder cancer and normal adjacent tissues using methylation-specific high-resolution melting (MS-HRM) analysis. Results showed that 73% (30/41) of transitional cell carcinoma, 100% (3/3) of squamous cell carcinoma, and 100% (4/4) of small cell carcinoma demonstrated promoter methylation of the RASSF1A or RASSF2A gene, but only 6% (1/16) of normal tissues had promoter methylation of RASSF genes. Testing positive for hypermethylation of RASSF1A or RASSF2A promoter provided 77% sensitivity and 94% specificity for identification of cancer tissues with an area under the curve of 0.854, suggesting that promoter methylation analysis of RASSF1A and RASSF2A genes has potential for use as a recurrence biomarker for bladder cancer patients.